Presenting the model of the role of professional ethics in creating a strategic advantage in the public sector administrative system - Farzin, Omid; Samiei, Rohollah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: professional ethics means philosophical value dos and don'ts towards oneself, others, and society, as well as the responsibility of the obligation that a person has in his profession towards others and society. Therefore, the purpose of this research is to provide a model of the role of professional ethics in creating a strategic advantage in the administrative system of the public sector of the Tax Affairs Organization of the northern provinces of the country. Methodology: This research is exploratory in nature, practical in terms of purpose, and mixed in terms of the data collection method. The first stage includes qualitative research and the fuzzy Delphi method, and then the quantitative research method. The method of collecting data in the first stage is by reading related texts and using the interview tool in an exploratory and semi-structured way. In the second step, the structural model of the relationships between dimensions and model indicators and the model fit was examined using the structural equation modeling method and using PLS software. Results: The results of the research showed that the answers of the experts led to 5 dimensions and 15 indicators of professional ethics and four dimensions and 12 indicators of strategic advantage, as well as the variables of social responsibility and knowledge management as mediating variables, and then the final model of the research was drawn. Considering the many challenges faced by Iran's economic organizations today, it is necessary to improve and ensure compliance with ethics. One of the fields that the tax affairs organization should pay special attention to is the field of professional ethics. Conclusion: Therefore, considering the importance of these dimensions and indicators, the management should consider and strengthen them in the work environment so that the effects of the role of professional ethics in creating a strategic advantage can be achieved.